Understanding Pain Catastrophizing: Putting Pieces Together - Petrini, Laura; Arendt-Nielsen, Lars (Frontiers in Psychology, 2020)
The present narrative review addresses issues concerning the defining criteria and conceptual underpinnings of pain catastrophizing. To date, the concept of pain catastrophizing has been extensively used in many clinical and experimental contexts and it is considered as one of the most important psychological correlate of pain chronicity and disability. Although its extensive use, we are still facing important problems related to its defining criteria and conceptual understanding. At present, there is no general theoretical agreement of what catastrophizing really is. The lack of a consensus on its definition and conceptual issues has important consequences on the choice of the pain management approaches, defining and identifying problems, and promoting novel research. Clinical and research work in absence of a common theoretical ground is often trivial. It is very surprising that clinical and experimental work has grown extensively in the past years, without a common ground in the form of a clear definition of pain catastrophizing and overview of its conceptual basis. Improving the efficacy and efficiency of pan catastrophizing related treatments requires an understanding of the theoretical construct. So far, most interventions have only demonstrated modest effects in reducing pain catastrophizing. Therefore, clarifying the construct may be an important precursor for developing more targeted and effective interventions, thereby easing some of the burden related to this aspect of pain. In our review, we have extracted and de-constructed common elements that emerge from different theoretical models with the aim to understand the concept of catastrophizing, which components can be modulated by psychological interventions, and the general role in pain processing. The analysis of the literature has indicated essential key elements to explain pain catastrophizing: emotional regulation, catastrophic worry (as repetitive negative thinking), rumination, behavioral inhibition and behavioral activation (BIS/BAS) systems, and interoceptive sensitivity. The present paper attempts to integrate these key elements with the aim to re-compose and unify the concept within a modern biopsychosocial interpretation of catastrophizing.